Implementasi Algoritma Genetika Dalam Optimasi Penjadwalan Mata Kuliah Mengunakan PHP Dan MySQL - Surya Sahri Ramadhan; Noveri Lysbetti M (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Currently scheduling courses at S1 Informatics Engineering University of Riau University is still done manually. Such a process requires a lot of accuracy and a lot of time, so there is a possibility of a clash of schedules which results in delays in the teaching and learning process. To overcome this, this study applies the Genetic Algorithm in the Course Scheduling System to shorten the time making schedule and help solve scheduling problems. Variables used include Lecturer Data, Room Data, Course Data, and Learning Hours Data. The output is Optimal Lecture Schedule without any restrictions that are not met. The testing of the system produces an optimal schedule and there is no clash in the 255th iteration when using 1000 iterations without the limitations of Room and Hours.Keywords : Algoritma Genetika, Penjadwalan Mata Kuliah, PHP, MySQL..